Perlindungan Hak Asasi Manusia Terhadap Tersangka Yang Ditahan Menurut Sistem Peradilan Pidana - Sulistiawati, Sulistiawati; Nurlindawati, Nurlindawati; Yunita, Nita; Ambarini, Siti Nur; Herawati, Herawati (Legalitas: Jurnal Hukum, 2025)
Suspects who are determined to be detained, based on the Criminal Procedure Code, have rights as detainees or suspects or defendants in the criminal justice system so that in the implementation of investigations and inquiries, law enforcers must be professional in carrying out their duties so that there are no violations of human rights and establish harmonious relationships with detainees, so the purpose of writing this article is to find out and analyze the protection of human rights for suspects who are detained according to the criminal justice system with a literature study research method, a descriptive qualitative approach